High‐resolution stratigraphy of Quaternary fluvial deposits in the Makó Trough and the Danube‐Tisza Interfluve, Hungary, based on magnetic susceptibility data. (7th October 2020) - Püspöki, Zoltán; Fogarassy‐Pummer, Tímea; Thamó‐Bozsó, Edit; Falus, György; Cserkész‐Nagy, Ágnes; Szappanos, Bálint; Márton, Emő; Lantos, Zoltán; Szabó, Szilárd; Stercel, Ferenc; Tóth‐Makk, Ágnes; Mcintosh, Richard W.; et al.
Abstract : High‐resolution stratigraphical architecture of a Quaternary fluvial succession in the Makó Trough and the Danube‐Tisza Interfluve (Pannonian Basin, Hungary) was investigated based on low field magnetic susceptibility (MS) measurements of seven fully cored boreholes, interpreted on the basis of the early postglacial magnetic susceptibility episodes previously described in the Körös and Jászság Basins. To confirm the reliability of the Dévaványa and Vésztő MS records (Körös Basin), the published magnetostratigraphical data were re‐investigated revealing the consequent arrangement of the MS peaks correlated with the Jingbian section and the short‐lived polarity reversals correlated with the Geomagnetic Instability Time Scale. The Quaternary climatic regime in the Körös Basin begins in the late Pliocene at 2.7 Ma. The correlation between the Körös Basin (Dévaványa) and Makó Trough (Mindszent) was confirmed by the multi‐proxy spectral investigation of the Mindszent section, revealing 100‐ and 41‐ka cycles in the MS, colour, logged spontaneous potential and resistivity records. Based on MS records of the seven boreholes, the base of the Quaternary can be identified irrespective of the facies, age and climatic phase of the lowermost Quaternary strata. By performing MS and log correlation of 131 boreholes, extended unconformities were detected in the Quaternary profiles in the Danube‐Tisza Interfluve ( 1070±10, 1920±10 and 2300±10 ka) interpreted as sequence boundaries. Sedimentological and mineralogical data reveal a significant change at 725–606 ka likely as a response to the 'mid‐Pleistocene transition', leading to the multiple branching of the Danube. SEM data revealed that ilmenite is also responsible for the development of the early postglacial magnetic susceptibility episodes. This increases the stratigraphical potential of fluvial successions with catchment area that contain metamorphic rocks. A gradual retreat of permafrost zone determines long‐term temporal trends of the climatically controlled fluvial magnetic susceptibility episodes, causing upward decreasing trends in the time series.